Mediasi Sebagai Alternatif Penyelesaian Sengketa Perceraian Akibat Kekerasan Dalam Rumah Tangga - Made Adityaswara Amerta Yoga S; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Fakultas Hukum, Universitas Warmadewa, 2022)
The current of globalization has affected the life of the Indonesian nation, especially in the field of law and economics. However, so far, it has not become a necessity for community traffic practices. Increasing intensity in the family, not only gives rise to higher and higher life dynamics, but will also increase the intensity of conflicts between husband and wife. This research method uses a normative type of legal research, namely by taking a statutory approach that examines applicable laws and regulations and takes a conceptual approach, namely examining literature materials in the form of theories, opinions of legal experts, and others related to the problem. The results of the study said that the position and function of Mediation in the settlement of divorce disputes, is to control the process and affirm the basic rules in this case Mediation is authorized to control the mediation process from beginning to end and facilitate the meeting of the parties and assist the parties in conducting negotiations, as well as Mediation maintains the structure and momentum in negotiations. Mediation has the authority to maintain and maintain the structure and momentum in negotiations, where the parties are given the opportunity to conduct talks and bargain in resolving disputes and ending the process when the mediation is no longer productive, in the mediation process it is often found that the parties are very difficult to discuss openly. They adhere to strict and rigid principles, especially during negotiations, and their mediation function is as catalysts, educators, translators, resource persons, bad news anchors, agents of reality, and scapegoats.